2018
DOI: 10.1007/s10549-018-5021-6
|View full text |Cite
|
Sign up to set email alerts
|

The flaxseed lignan secoisolariciresinol diglucoside decreases local inflammation, suppresses NFκB signaling, and inhibits mammary tumor growth

Abstract: Purpose Exposure to the polyphenolic plant lignan secoisolariciresinol diglucoside (SDG) and its metabolite enterolactone (ENL) has been associated with reduced breast cancer progression, particularly for estrogen receptor alpha (ERα)-negative disease, and decreased preclinical mammary tumor growth. However, while preclinical studies have established that SDG and ENL affect measures of progression in models of triple-negative breast cancer (TNBC, a subset of ERα-negative disease), the molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Studies under various cellular and animal models have demonstrated that SDG has potent bioactivity in reducing the risk of cancer, ameliorating oxidative stress, preventing diabetes, and protecting from neurodegenerative disease, such as Alzheimer's disease and Parkinson's disease [ 8 , 9 ]. SDG could reduce tumor growth via inhibiting the activity of nuclear factor kappa-B in murine E0771 cells (a model of triple-negative breast cancer) [ 10 ]. SDG is also a potent angiotensin-converting enzyme (ACE) inhibitor [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies under various cellular and animal models have demonstrated that SDG has potent bioactivity in reducing the risk of cancer, ameliorating oxidative stress, preventing diabetes, and protecting from neurodegenerative disease, such as Alzheimer's disease and Parkinson's disease [ 8 , 9 ]. SDG could reduce tumor growth via inhibiting the activity of nuclear factor kappa-B in murine E0771 cells (a model of triple-negative breast cancer) [ 10 ]. SDG is also a potent angiotensin-converting enzyme (ACE) inhibitor [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that much of the effect of lignans may be as a result of antiinflammatory influences, which we have not as yet adequately explored in our clinical trial specimens [55][56][57]. Indeed, our companion study in an immunocompetent mouse model of triple negative breast cancer suggested that SDG, in doses producing equivalent enterolactone and enterodiol blood levels as in our human pilot study, suppressed NFκB activation [14]. This was associated with growth suppression of triple negative breast cancer with high initial levels of NFκB.…”
Section: Discussionmentioning
confidence: 79%
“…In preclinical studies SDG significantly increased gene and protein levels of the antioxidants HO-1, GSTM1 and NQO1 [13]. SDG may also reduce NFκB pro-inflammatory signaling through inhibition of p65 phosphorylation, as we have demonstrated in a preclinical model [14]. Although NFκB is classically activated by oxidative stress and inflammatory cytokines, it can also be activated by Receptor Activator of NFκB (RANK) which in turn is upregulated via hormonal stimulation and progesterone receptor activation [15,16].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Epidemiological studies have revealed that higher dietary intake of EL precursors and higher serum concentrations of EL are correlated with decreased breast cancer risk and mortality, as well as more satisfactory survival time, particularly in postmenopausal breast cancer patients. 433 In animal experiments, EL exerts its antibreast cancer functions by inhibiting NF-κB-mediated inflammation, 434 TGF-β-induced EMT, 435 and cancer cell viability. 436 Collectively, the gut microbiome potentially affects carcinogenesis through its far-reaching impacts on estrogen metabolism, energy metabolism, and the anti-tumor function of the immune system.…”
Section: Figmentioning
confidence: 99%